A HAWAIIAN BEGINNING FOR THE ICELAND PLUME: MODELLING OF RECONNAISSANCE DATA FOR OLIVINE-HOSTED MELT INCLUSIONS IN PALAEOGENE PICRITE LAVAS FROM EAST GREENLAND - Nielsen T.F.D.; Turkov V.A.; Kogarko L.N.; Solovova I.P.; Ryabchikov I.D. (My University, 2006)
Compositions of parental and primary melts are modelled for olivine-hosted melt inclusions in three, Palaeogene, proto-Iceland plume picrite samples from East Greenland. The samples represent three stages in the magmatic evolution: (1) the early pre-spreading volcanics of the Lower Basalts, (2) the early plateau basalts in the Milne Land Formation and (3) the steady stage plateau basalt of the Geikie Plateau Formation. The observations suggest that the host lavas are variably mixed with melts and material from the wall rocks of the feeder system. Pressure estimates based on KD between olivine and reconstructed melt composition suggests the melts to be trapped in their hosts during ascent from magma chambers near the base of the East Greenland crust. CaO/Al2O3 ratios suggest initiation of melting in the proto-Iceland plume at pressures up to 5-6 GPa and segregation depths mainly between 3 and 4 GPa. Early melts show marked similarities in major and trace elements with primary Hawaiian type melts. It is proposed that the continental separation in the North Atlantic was influenced by a pre-seafloor spreading rise of a "Hawaiian" type plume with a significant component of recycled basalt. © 2006 Elsevier B.V. All rights reserved.
Keywords: EAST GREENLAND; HAWAIIAN TYPE; MELT INCLUSIONS; PALAEOGENE; PICRITES; PRIMARY MELTS